175k views
0 votes
: Show that the propositions (p ∨ q) ∧ (¬p ∨ r) and (p ∧ r) ⊕ (¬p ∧ q) are logically equivalent.

User Dkris
by
5.3k points

1 Answer

5 votes

Answer:


(p\vee q)\wedge(\\eg p\vee r)\equiv(p\wedge r)\vee(\\eg p\wedge q)

Step-by-step explanation:

The statements are logically equivalent if they have the same truth tables. So let´s use truth tables in order to determine if they are logically equivalent or not:

The picture that I attached you shows the truth table for each case. As you can see in the highlight columns:


(p\vee q)\wedge(\\eg p\vee r)\equiv(p\wedge r)\vee(\\eg p\wedge q)

They are logically equivalent because they have exactly the same truth values between each other. Hence, we can conclude that they are logically equivalent.

: Show that the propositions (p ∨ q) ∧ (¬p ∨ r) and (p ∧ r) ⊕ (¬p ∧ q) are logically-example-1
User Torbinsky
by
5.5k points